2012
DOI: 10.3389/fphys.2012.00050
|View full text |Cite
|
Sign up to set email alerts
|

Erythropoietin Treatment Enhances Muscle Mitochondrial Capacity in Humans

Abstract: Erythropoietin (Epo) treatment has been shown to induce mitochondrial biogenesis in cardiac muscle along with enhanced mitochondrial capacity in mice. We hypothesized that recombinant human Epo (rhEpo) treatment enhances skeletal muscle mitochondrial oxidative phosphorylation (OXPHOS) capacity in humans. In six healthy volunteers rhEpo was administered by sub-cutaneous injection over 8 weeks with oral iron (100 mg) supplementation taken daily. Mitochondrial OXPHOS was quantified by high-resolution respirometry… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
46
1
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 42 publications
(52 citation statements)
references
References 27 publications
4
46
1
1
Order By: Relevance
“…A previous study demonstrated that exogenous erythropoietin treatment resulted in an increase of hemoglobin concentration leading to increased oxygen delivery and improved exercise capacity. [12][13][14][15] These results seem at first sight to be opposite to our results. However, we assessed that exercise training decreased RDW leading to increase oxygen binding with hemoglobin and oxygen delivery, and improved exercise capacity.…”
Section: )contrasting
confidence: 57%
“…A previous study demonstrated that exogenous erythropoietin treatment resulted in an increase of hemoglobin concentration leading to increased oxygen delivery and improved exercise capacity. [12][13][14][15] These results seem at first sight to be opposite to our results. However, we assessed that exercise training decreased RDW leading to increase oxygen binding with hemoglobin and oxygen delivery, and improved exercise capacity.…”
Section: )contrasting
confidence: 57%
“…Participants also performed another graded cycling exercise test (test 2) until exhaustion to confirm the VO 2max values from test 1. The detailed description of test 2 has been reported in Plenge et al 2012. No differences were observed between VO 2max values measured by either test 1 or 2.…”
Section: General Proceduresmentioning
confidence: 95%
“…Results describing basic haematological changes are shown in Table I, whereas maximal mitochondrial respiratory capacity and haematocrit changes after EPO administration to these participants have already been published (Plenge et al, 2012). Participants were asked to maintain their daily physical activity level as usual throughout the entire study.…”
Section: Participantsmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, recombinant protein increases OXPHOS in human skeletal muscle (Plenge et al, 2012). The enhancement and recovery of cellular functions through stimulation of hemoglobin production and mitochondrial activity in nonhematopoietic cells by EPO-like drugs might be a testable therapeutic strategy for certain ischemic or mitochondrial diseases in carefully selected patient populations, although the procoagulant effects of EPO administration have raised a legitimate caution.…”
Section: A Estrogens Erythropoietin and Thyroid Hormonementioning
confidence: 99%